Financial burden associated with time to return to work after living kidney donation. Issue 1 (20th June 2018) - Larson, Dawn B.; Wiseman, Jennifer F.; Vock, David M.; Berglund, Danielle M.; Roman, Ashley M.; Ibrahim, Hassan N.; Matas, Arthur J.
Abstract : Many living kidney donors undertake a significant financial burden in order to donate. We studied the association between time to return to work and reported financial burden. Kidney donors who donated from 2/2005 through 12/2015 (n = 1012) were surveyed 6 months after donation and asked about occupation, time to return to work, and financial burden (on a 10‐point Likert scale). Of 856 donors working for pay, 629 (73%) responded. After adjusting for donor characteristics, increased length of time to return to work was a significant predictor of financial burden ( P  < .001). It is notable that those in manual/skilled trade occupations, compared with all other occupations, experienced greater financial burden for each week away from work ( P  = .003). Older age at donation and nondirected (vs directed) donation were associated with significantly decreased financial burden. These observations provide additional information to better inform donor candidates, and further emphasize the need to develop policies so that living kidney donation can be financially neutral. Abstract : Increased length of time to return to work is a significant predictor of financial burden, with those in manual/skilled trade occupations, compared with all other occupations, experiencing greater financial burden for each week away from work.